Pelatihan Berkarya Recycle Art untuk Mewujudkan Siswa Kreatif di SMP PGRI 13 Gondangrejo Karanganyar - Yulianto, Nanang; Sulistyo, Edy Tri (DEDIKASI: Community Service Reports, 2022)
The realization of creative students is one of the learning objectives implemented in schools. Students become creative when faced with  contextual problems at school.  Theproblem of plastic waste  at SMP PGRI 13 Gondangrejo Karanganyar encouragesschool residents to choose creative solutions through the useof plastic waste mineral water bottles for the manufacture of recycle art works  that are charged with creativity.  The purpose of this  activity is to increase students' creativity   in creating recycle art using plastic waste contained in the school environment. The implementation of training and mentoring activities uses lecture and question and answer methods in the delivery of theory, while experimental methods are used when practicing work. The application of this method is supported by the proximity of si participation and collaborasi dari in the early to late stages.  The achievements of the  activities are: (1) The realization  of recycle art works in the  form of  various types  of plastic flowers  in the school garden located in front of the teacher's office so that  the  school environment becomes comfortable and beautiful, (2) Increasingstudent creativity in creating recycle art.